1997
DOI: 10.1093/humrep/12.11.2359
|View full text |Cite
|
Sign up to set email alerts
|

Dual suppression with oral contraceptives and gonadotrophin releasing-hormone agonists improves in-vitro fertilization outcome in high responder patients

Abstract: Certain patients have a tendency for high response to gonadotrophin therapy which is often not ameliorated with prior gonadotrophin-releasing hormone agonist (GnRHa) suppression. As a result, these patients are frequently cancelled and often experience ovarian hyperstimulation syndrome (OHSS) episodes during in-vitro fertilization (IVF)-embryo transfer cycles. Patients with polycystic ovarian syndrome (PCOS) have been noted to be particularly sensitive to exogenous gonadotrophin therapy. We have developed a pr… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

3
46
1
3

Year Published

2001
2001
2018
2018

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 106 publications
(53 citation statements)
references
References 33 publications
3
46
1
3
Order By: Relevance
“…Similarly, Biljan et al [18] reported the advantage of OC pretreatment during the long standard protocol of GnRH-a administration. Damario et al [19] also revealed that dual suppression with oral contraceptives and gonadotrophin releasing-hormone agonists improves invitro fertilization outcome in high responders. All of the above mentioned studies evaluated OCs used in normo and/or high responder patients during long luteal protocol.…”
Section: Discussionmentioning
confidence: 98%
“…Similarly, Biljan et al [18] reported the advantage of OC pretreatment during the long standard protocol of GnRH-a administration. Damario et al [19] also revealed that dual suppression with oral contraceptives and gonadotrophin releasing-hormone agonists improves invitro fertilization outcome in high responders. All of the above mentioned studies evaluated OCs used in normo and/or high responder patients during long luteal protocol.…”
Section: Discussionmentioning
confidence: 98%
“…Apart from the above-mentioned studies, available experience with leuprolide acetate and OCP is limited to studies evaluating hyperresponder [12] or poor responder [13,14] cohorts of women. Among high responder patients, premedication with an OCP might decrease the cancellation rate and increase both the clinical and ongoing pregnancy rates when compared with their previous IVF cycle without OCP pretreatment [12].…”
Section: Discussionmentioning
confidence: 99%
“…Marci et al [26] proposed a low-dose stimulation protocol (starting at 75 IU FSH, increased by 37.5 IU every 4 days) and they obtained a high implantation (21.8%) and pregnancy (38.4%) rates without cycle cancellation. Damario et al [27] proposed dual suppression with oral contraceptives and GnRHa, and 150 IU gonadotropin was initiated from day 3. Although a 46.5% pregnancy rate was achieved, 13 cycles (13.1%) were cancelled before embryo transfer.…”
Section: Discussionmentioning
confidence: 99%